2018
DOI: 10.12669/pjms.343.15012
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of orthodontic brackets detachment during orthodontic treatment: A systematic review

Abstract: Objectives:To evaluate the incidence of orthodontic brackets detachment during orthodontic treatment.Methods:Using electronic databases; eligible studies up to January 2018 were retrieved, independently reviewed, and screened. The Coleman Methodology Scoring System (CMS) and Cochrane Collaboration’s tool were used to assess quality and risk of bias in the included studies.Results:Of the seventeen studies included in the final synthesis, thirteen were categorized as randomized clinical trials (RCTs), one prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 37 publications
3
24
1
2
Order By: Relevance
“…The results attained were in accordance to those evaluated by Ryou (Ryou et al, 2008). However, contradictory results were shown by to Northrup et al and Lee et al where they reported an ARI score of 3 in 90% and 40% respectively (Almosa and Zafar, 2018;Soonthodu et al, 2018). The difference in the ARI scores could be due to the in luence of other variables such as study design, bracket base, and enamel pre-treatment.…”
Section: Adhesive Remnant Indexsupporting
confidence: 85%
“…The results attained were in accordance to those evaluated by Ryou (Ryou et al, 2008). However, contradictory results were shown by to Northrup et al and Lee et al where they reported an ARI score of 3 in 90% and 40% respectively (Almosa and Zafar, 2018;Soonthodu et al, 2018). The difference in the ARI scores could be due to the in luence of other variables such as study design, bracket base, and enamel pre-treatment.…”
Section: Adhesive Remnant Indexsupporting
confidence: 85%
“…There are a number of steps involved during the bonding of attachments on the tooth surface. Overall, bonding failure was found to be as low as 0.6% and as high as 28% [ 10 , 17 23 ]. In general, a bracket failure rate below 10% has been suggested to be clinically acceptable.…”
Section: Introductionmentioning
confidence: 99%
“…Orthodontic treatment using fixed appliances is based on the specific forces that is applied to the teeth through the attachment of brackets. [1] Extreme friction forces will impede the teeth movement and detract the efficacy of the appliances. [2] Friction is affected by biological factor-such as saliva, debris, and biodegradation of the appliance's components that has been used-and physical factor as the using of brackets, archwires, and ligations.…”
Section: Introductionmentioning
confidence: 99%